2021
DOI: 10.1371/journal.pone.0249098
|View full text |Cite|
|
Sign up to set email alerts
|

How to bring residents’ psychosocial well-being to the heart of the fight against Covid-19 in Belgian nursing homes—A qualitative study

Abstract: Background Nursing homes (NH) for the elderly have been particularly affected by the Covid-19 pandemic mainly due to their hosted vulnerable populations and poor outbreak preparedness. In Belgium, the medical humanitarian organization Médecins Sans Frontières (MSF) implemented a support project for NH including training on infection prevention and control (IPC), (re)-organization of care, and psychosocial support for NH staff. As psychosocial and mental health needs of NH residents in times of Covid-19 are poo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
100
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(111 citation statements)
references
References 35 publications
8
100
0
3
Order By: Relevance
“…Besides, our ndings showed that COVID-19-related burden at work (e.g., lack of personal protection equipment, a small number of COVID-19-Tests for residents and staff) was positively associated with the dissatisfaction with COVID-19 management of care home management, COVID-19-related anxiety, and dementia as a focus of care. This is in line with previous research showing that there was uncertainty about implemented hygiene measures due to a lack of communication and information and not being included in decision-making processes by care home management during the pandemic [8, 31,32,33]. A higher burden for care home staff working with residents with dementia, in general, was a concern even Loading [MathJax]/jax/output/CommonHTML/fonts/TeX/fontdata.js before the pandemic [34].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Besides, our ndings showed that COVID-19-related burden at work (e.g., lack of personal protection equipment, a small number of COVID-19-Tests for residents and staff) was positively associated with the dissatisfaction with COVID-19 management of care home management, COVID-19-related anxiety, and dementia as a focus of care. This is in line with previous research showing that there was uncertainty about implemented hygiene measures due to a lack of communication and information and not being included in decision-making processes by care home management during the pandemic [8, 31,32,33]. A higher burden for care home staff working with residents with dementia, in general, was a concern even Loading [MathJax]/jax/output/CommonHTML/fonts/TeX/fontdata.js before the pandemic [34].…”
Section: Discussionsupporting
confidence: 91%
“…Prior research showed that care home staff often did not feel involved in decision-making processes and did not feel heard by the management of their care homes. A lack of communication between management and staff caused uncertainty and distress about handling the pandemic and implementing measures to prevent infections [31,32,33].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the results obtained from the present study, one study reported that the mean BRS score was 19.41±2.67 in individuals over the age of 65 during the COVID-19 process. 19 Psychological resilience refers to an individual's ability to successfully overcome adverse conditions and adapt to a new situation. 36 While loneliness, negative feelings, and mental illness negatively affect resilience, 45 , 49 , 50 well-being, social networking, and positive feelings positively affect resilience.…”
Section: Discussionmentioning
confidence: 99%
“… 9 , 17 The restrictive measures, fear, and loneliness could adversely affect the physical, psychological, mental health, life style, and quality of life (QOL) of older adults. 5 , 17 , 18 , 19 , 20 …”
Section: Introductionmentioning
confidence: 99%
“…Yet, the medical and staffing needs of residents were simultaneously surging, forcing many sick (and infectious) caregivers back into the workplace. The cycle was compounded by the destructive effects that an enormous workload and an anxiety-producing work environment is known to have on caregivers' wellbeing [12,18,20,21,36].…”
Section: Discussionmentioning
confidence: 99%